Performance Assessment of the First Year Engineering Students using Force and Motion Conceptual Evaluation (FMCE) - Exedy C. Lampara (Basic and Applied Education Research Journal, 2022)
The admission of non-STEM graduates to engineering programs creates an opportunity to determine if the Senior High School strand does really dictate the performance of students. This study administered the Force and Motion Conceptual Evaluation (FMCE) to the first-year engineering students to determine if STEM graduates perform better than non-STEM graduates. The FMCE was administered to six hundred-seven (n = 607) first year engineering students of a state-run university in the Philippines, school year 2019-2020 and 2020-2021. The results reveal that there is no significant difference between the mean scores obtained by the STEM and non-STEM graduates (p = 0.912) in the FMCE. It was noted that the students who graduated from private and public high schools have similar performance (p = 0.242). Nevertheless, there is an urban-rural gap in performance among the respondents, where students who graduated from schools in cities have better performance than those who graduated from rural schools (p = 0.019). Finally, in the field dominated by male, the results suggest that female students are at par with male student students (p = 0.123) and both have statistically the same level of confidence with their answers (p = 0.176).